Penguatan Ekonomi Lokal Pada Pelaku Umkm Berbasis Digital - Falah, Asep saeful; Yunita Puspita Dewi; Tedi Firdaus; Muhamad Hilmi Ruby; Meta Amelia; Rena Hermayanti; Nadila Rosinta; I, Galih Hamzah Noor; Windasari; Mayang Dwi Nurmalia; Saeful Ramdan; Ai Sri Mulyani (CV. SINAR HOWUHOWU, 2025)
The Thematic Community Service (KKNT) program conducted by STIE LM students in Padakembang Village for 44 days successfully identified significant creative economic potential in the village, particularly in the local resource-based UMKM sector. Products such as modern and simple bamboo weaving, table making, pots, iron ornaments, palm sugar, traditional food (gendar), and caterpillar have a relatively high market demand. However, the main problem faced by UMKM actors is their reliance on middlemen and collectors in marketing their products, as well as traditional and poorly recorded financial management. Through a series of activities, KKNT students sought to provide solutions to these problems. One of the efforts made was to hold a seminar themed